(untitled) (GYMNASIUM, 2017)
This study was designed to investigate the relative effects of observing video, point-light, and stick-figure model demonstrations on the development of internal motor representation of a highly complex sport skill. Forty one novice female and male students were randomly assigned to video, point-light, stick-figure and no-demonstration control groups. Internal motor representation was evaluated by a computer - based test using the error detection paradigm. Participants had to view ten digital photos representing different phases of a Baseball pitching and were instructed to identify by mouse-clicking various movement errors. The test was respectively performed after 5 familiarization trials (pre-test), 3 acquisition blocks of 10 trials (post-test) and one week without practice (retention test). Participants observed related model demonstrations prior to each acquisition block. Results showed that demonstration groups improved their scores in either post-test or retention test; however these improvements were not statistically significant. Moreover, there was no significant difference between groups either in post-test or retention test. The findings are discussed in terms of difficulty of errors, insufficient amount of physical or observational practice, and small sample size.